Closed state-coupled C-type inactivation in BK channels - Yan, Jiusheng (Proc Natl Acad Sci U S A, 2016)
Ion channels regulate ion flow by opening and closing their pore gates. K(+) channels commonly possess two pore gates, one at the intracellular end for fast channel activation/deactivation and the other at the selectivity filter for slow C-type inactivation/recovery. The large-conductance calcium-activated potassium (BK) channel lacks a classic intracellular bundle-crossing activation gate and normally show no C-type inactivation. We hypothesized that the BK channel’s activation gate may spatially overlap or coexist with the C-type inactivation gate at or near the selectivity filter. We induced C-type inactivation in BK channels and studied the relationship between activation/deactivation and C-type inactivation/recovery. We observed prominent slow C-type inactivation/recovery in BK channels by an extreme low concentration of extracellular K(+) together with a Y294E/K/Q/S or Y279F mutation whose equivalent in Shaker channels (T449E/K/D/Q/S or W434F) caused a greatly accelerated rate of C-type inactivation or constitutive C-inactivation. C-type inactivation in most K(+) channels occurs upon sustained membrane depolarization or channel opening and then recovers during hyperpolarized membrane potentials or channel closure. However, we found that the BK channel C-type inactivation occurred during hyperpolarized membrane potentials or with decreased intracellular calcium ([Ca(2+)](i)) and recovered with depolarized membrane potentials or elevated [Ca(2+)](i). Constitutively open mutation prevented BK channels from C-type inactivation. We concluded that BK channel C-type inactivation is closed state-dependent and that its extents and rates inversely correlate with channel-open probability. Because C-type inactivation can involve multiple conformational changes at the selectivity filter, we propose that the BK channel’s normal closing may represent an early conformational stage of C-type inactivation.